1997
DOI: 10.1507/endocrj.44.181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CL316,243, a Highly Specific .BETA.3-Adrenoceptor Agonist, on Lipolysis of Epididymal, Mesenteric and Subcutaneous Adipocytes in Rats.

Abstract: Abstract. To clarify whether a -adrenoceptor agonist is more lipolytic in the visceral adipocytes than in the subcutaneous adipocytes, the lipolysis induced by CL316,243, a highly specific f3-adrenoceptor agonist (relative selectivities of 0, 1 and 100,000 for flu-, r2-and r3-receptors, respectively) was investigated in adipose tissue from rats. White adipocytes were prepared from the subcutaneous, mesenteric, and epididymal white adipose tissues of male Wistar rats (weighing about 150 g). Our findings showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…Moreover, changes in RAB18 protein content in adipose tissue samples induced by fasting were similar to those observed for Rab18 mRNA. These observations are in accordance with the higher expression levels of b-adrenergic receptors and increased b-adrenergic stimulation of lipolysis exhibited by visceral, compared with subcutaneous, WAT (Hoffstedt et al 1997, Umekawa et al 1997, Portillo et al 2000. Moreover, visceral fat is more responsive to fasting conditions than subcutaneous fat with regard to the induction of the lipolytic enzymes, hormone-sensitive lipase (HSL; Akesson et al 2003), and adipose triglyceride lipase (ATGL; Palou et al 2010).…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, changes in RAB18 protein content in adipose tissue samples induced by fasting were similar to those observed for Rab18 mRNA. These observations are in accordance with the higher expression levels of b-adrenergic receptors and increased b-adrenergic stimulation of lipolysis exhibited by visceral, compared with subcutaneous, WAT (Hoffstedt et al 1997, Umekawa et al 1997, Portillo et al 2000. Moreover, visceral fat is more responsive to fasting conditions than subcutaneous fat with regard to the induction of the lipolytic enzymes, hormone-sensitive lipase (HSL; Akesson et al 2003), and adipose triglyceride lipase (ATGL; Palou et al 2010).…”
Section: Discussionsupporting
confidence: 61%
“…[31][32][33] Although it has been suggested that because chronic administration of the β 3 -adrenoceptor agonist CL-316 243 differentially stimulates browning across WAT depots, 31 this does not necessarily imply that there is a cell autonomous process at work in browning independent of the CNS control of sympathetic drive as some suggest. 1 This effect could easily be explained in terms of the number and affinity of β 3 -adrenoceptors that occur across WAT depots (for example, see Bowen et al, 34 Leibel and Hirsch, 35 Umekawa et al 36 ) or the balance between lipolytic/browning β 3 -adrenoceptors and antilipolytic (and perhaps anti-browning) α 2 -adrenoceptors (for review, see Lafontan et al 37,38 ). The post-β-adrenoceptor signaling cascade responsible for either the transdifferentiation of white to brite/beige or de novo creation of brite/beige adipocytes will not be reviewed here.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in We also tested the effects of OPC 3911 and RO 20-1724 on insulin-induced glucose uptake in the presence of pituitary adenylate cyclase-activating peptide (PACAP) and CL316243 (β 3 -adrenergic receptor agonist), which through interaction with G-protein linked receptors increase cAMP and lipolysis [29,30]. The inhibitory effect of OPC3911 on insulin-induced glucose uptake was potentiated in the presence of both PACAP and CL316243 (data not shown) as was the case for isoproterenol.…”
Section: Pde3b Regulates Insulin-induced Glucose Uptake Glut-4 Transmentioning
confidence: 99%